IL-12 PE, CD 69 PERCP, CD3 FITC, AND CD4 APC OPTIMIZATION WITH ACTIVATION OF ISOLATED AGENT HEAT-KILLED SONICATED MYCOBACTERIUM TUBERCULOSIS BEIJING STRAIN - RINI SUNDARI; IDA PARWATI; JOHANES C. MOSE; BUDI SETIABUDIAWAN (Syiah Kuala University, 2014)
Infection caused by Mycobaterium tuberculosis exists in form of intracellular infection, which leads to lymphocyte activation. CD69 is the first lymphocyte activation marker expressed in Th1 lymphocyte, which follows by IL-12 release. Flow cytometry analysis can identify the subpopulations of lymphocytes and intracellular cytokines such as IL-12, yet precise preparation needs to be done. This research aims to conduct optimization with four color lyse/wash flow cytometry assay system FastImmune™ FACSCalibur examination, with monoclonal antibody IL-12, CD69, CD3, and CD4 in succession uses fluorochrome PE, PerCP, FITC, and APC.To activate the lymphocytes from heparinized whole blood, we used activation agent which derives from isolated heat-killed sonicated Mycobacterium tuberculosis Beijing strain. Optimal concentration from the according activation agents is 40 mL. To determine the compensation, BDTM CompBead and blank-cell unstainning are used, but the maximum result showed by blank-cell unstainning.Each monoclonal antibody dosage of IL-12PE, CD69 PerCP, and CD3 FITC is 40 mL, while CD4 APC 5 mL. Total event lymphocyte is determined minimally by 10,000 events. With 18,510 total events and Th gated events quantity are 4,692, the result obtained is IL12-PE has 7.4% gated (347 events); CD69+ perCP/CD3+ FITC 18.2% (850 events); and CD69+ perCP/CD4+ APC 3.9%.